Taire ou exposer la diversité sexuelle ? Impacts des normes de genre et de l'hétéronormativité sur les pratiques enseignantes - Richard, Gabrielle (Genre, sexualité & société, 2015)
À partir de 22 entretiens et de 243 questionnaires d’enquête complétés par des enseignants du secondaire du Québec (Canada), cet article interroge l’existence de normes relatives au genre et à l’orientation sexuelle en milieu scolaire. Les résultats suggèrent que les pratiques professionnelles des enseignant(e)s, tant lesbiennes, gais et bisexuels (LGB) qu’hétérosexuel(le)s concernant l’homophobie et la diversité sexuelle sont influencées par ces normes. Trente ans après les premiers travaux sur le vécu des enseignants LGB, la littérature sur le coming out demeure centrale pour comprendre les pratiques professionnelles de ceux-ci ainsi que leurs appréhensions. Based on 22 interviews and 243 survey questionnaires filled out by high school teachers in Québec (Canada), this paper questions the existence of norms relating to gender and sexual orientation in schools. Results suggest that teachers’ professional practices regarding homophobia and sexual diversity are influenced by these norms, whether they identify as heterosexual or as lesbian, gay or bisexual (LGB). Thirty years after the first studies on LGB teachers’ experiences, the coming out literature remains central to the understanding of teachers’ apprehensions and fears, as well as their pedagogical practices.
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; homophobie; hétérosexisme; identités LGBTQIA2+; québec; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire; étude qualitative; étude quantitative

The pedagogical practices of Québec high school teachers relative to sexual diversity - Richard, Gabrielle (Journal of LGBT Youth, 2015)
This article explores the ways in which teachers describe their pedagogical and intervention practices relative to sexual diversity in Québec (Canada). Three variables closely associated with teachers who report inclusive practices emerge: experiential training (based on the experience of a lesbian, gay, or bisexual [LGB] teacher), contact training (from close acquaintance with LGB individuals), and professional training. These factors impact the probability that a teacher will refer to homosexuality, intervene when homophobic incidents occur to deconstruct prejudices, and become the confidant of LGBQ students. Results are discussed based on research on minority teachers and on the roles of straight allies in education.
Number: 2 https://www.researchgate.net/publication/276111985_The_Pedagogical_Practices_of_Quebec_High_School_Teachers_Relative_to_Sexual_Diversity
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; formations; homophobie; hétérosexisme; identités LGBTQIA2+; outils; québec; ressource en ligne; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle